Phosphorylation sites in the Hook domain of CaVβ subunits differentially modulate CaV1.2 channel function. (October 2015) - Brunet, Sylvain; Emrick, Michelle A.; Sadilek, Martin; Scheuer, Todd; Catterall, William A.
Abstract: Regulation of L-type calcium current is critical for the development, function, and regulation of many cell types. CaV 1.2 channels that conduct L-type calcium currents are regulated by many protein kinases, but the sites of action of these kinases remain unknown in most cases. We combined mass spectrometry (LC–MS/MS) and whole-cell patch clamp techniques in order to identify sites of phosphorylation of CaV β subunits in vivo and test the impact of mutations of those sites on CaV 1.2 channel function in vitro. Using the CaV 1.1 channel purified from rabbit skeletal muscle as a substrate for phosphoproteomic analysis, we found that Ser 193 and Thr 205 in the HOOK domain of CaV β1a subunits were both phosphorylated in vivo. Ser 193 is located in a potential consensus sequence for casein kinase II, but it was not phosphorylated in vitro by that kinase. In contrast, Thr 205 is located in a consensus sequence for cAMP-dependent phosphorylation, and it was robustly phosphorylated in vitro by PKA. These two sites are conserved in multiple CaV β subunit isoforms, including the principal CaV β subunit of cardiac CaV 1.2 channels, CaV β2b . In order to assess potential modulatory effects of phosphorylation at these sites separately from the effects of phosphorylation of the α1 1.2 subunit, we inserted phosphomimetic or phosphoinhibitory mutations in CaV β2b and analyzed their effects on CaV 1.2 channel function in transfected nonmuscle cells. The phosphomimetic mutation CaV β2b S152E decreased peak channel currents and shifted the voltage dependence of both activation and inactivation to more positive membrane potentials. The phosphoinhibitory mutation CaV β2b S152A had opposite effects. There were no differences in peak CaV 1.2 currents or voltage dependence between the phosphomimetic mutation CaV β2b T164D and the phosphoinhibitory mutation CaV β2b T164A . However, calcium-dependent inactivation was significantly increased for the phosphomimetic mutation CaV β2b T164D . This effect was subunit-specific, as the corresponding mutation in the palmitoylated isoform, CaV β2a, had no effect. Overall, our data identify two conserved sites of phosphorylation of the Hook domain of CaV β subunits in vivo and reveal differential modulatory effects of phosphomimetic mutations in these sites. These results reveal a new dimension of regulation of CaV 1.2 channels through phosphorylation of the Hook domains of their β subunits. Highlights: Ca 2 + channel β subunits are phosphorylated on two sites in the Hook domain in vivo. Ser152 in CaV β2b has a casein kinase II consensus sequence; Thr 164 is a PKA site. Phosphomimetic mutation S152E in CaV β2b decreased peak current and shifted activation. Phosphomimetic mutation T164D in CaV β2b increased Ca 2 + -dependent inactivation. Phosphorylation of sites in the Hook domain may regulate CaV 1.2 channels in vivo.